PELATIHAN PEMBUATAN MEDIA INTERAKTIF MENGGUNAKAN APLIKASI CLASSPOINT UNTUK MENGOPTIMALKAN PEMBELAJARAN DI SEKOLAH DASAR - Indraswati, Dyah; Sobri, Muhammad; Rahmatih, Aisa Nikmah; Fauzi, Asri; Amrullah, Lalu Wira Zain (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2023)
So far, the use of PowerPoint is only for media presentations or teaching materials that are one-way in nature. Presentations using PowerPoint are commonly used, especially by teachers at SDN 14 Cakranegara. This service seeks to further optimize learning with applications that can be integrated with the use of PowerPoint. The application is called Classpoint which is an interactive media that can load learning material in the form of questions, quizzes, or questions. The types of questions provided by Classpoint which can be accessed for free include multiple choice, short answer, word cloud, slide drawing, image upload with competition mode, and other settings. the methods of implementing the service that will be carried out include presentations by the lecturer team, question, and answer activities and discussions, as well as direct assistance in making Classpoint interactive media. The training at SDN 14 Cakranegara was conducive because the 10 participants were guided by 5 service team members and 2 students so that obstacles could be overcome immediately. The presenters were very communicative and guided step by step and ensured that each participant could go through each step before moving on to the next step. In the training of the five types of Classpoint interactive quiz features such as multiple choice, word clouds, short answers, slide drawings, and image uploads, all of them can be applied.